Minerological and physico-chemical properties of the building materials of Koule castle, Heraklion, Crete. - Karampatsou, G.; Markopoulos, Th.; Repouskou, E.; Triantafyllou, G. (Bulletin of the Geological Society of Greece, 2013)
This study was designed to determine the physical and technical characteristics of the building stones and mortars of the Koule Castle Heraklion, in order to use compatible materials in future restoration works. Five core samples of rocks and masonry mortars have been extracted from different parts of the monument. Both mortar and rock samples have been studied by optical microscopy and X-ray diffraction (XRD). Their morphological characteristics, granulometry and mineralogical composition have been determined. In the old mortars a thermogravimetric analysis was carried out, while mortar samples have also been studied by scanning electron microscopy. The building stones of Koule Castle are in their majority biomicritic breccia limestones and bioclastic limestones. The binder of the studied mortars consists of calcite, as a result of the lime carbonation. The inert material of the mortars consists mainly of calcite and secondarily of quartz. The inert to binder material ratio was determined by volume from 1/0,96 to 2,6 /1. In conclusion, the mortars to be used in future restoration works, should consist of compatible materials to the old mortars. The inert materials of the mortars should consist of quartz (70%) and secondarily of calcite (30%) and the binder of hydraulic lime NHL 3.5, in an inert material/ binder ratio of 2,5 /1, in order to protect the mortars against marine corrosion.